Transferência de renda e educação: uma análise longitudinal de impacto do Programa Bolsa Família em 2005-2009 - Vinicius do Prado Monteiro (2014)
This work has the main objective of analyzing the impact of Bolsa Família Program on school attendance and flow, latter measured by the promotion, repetition and evasion. The analysis focuses on measuring the effects of the program in two main dimensions: i) receipt effect, for families who became beneficiaries of the program in the last four years and; ii) lasting effect, for families who have been receiving the benefit for more than four years. The data used is from the Bolsa Família Program Evaluation, developed by the Ministry of Social Development, which is a longitudinal research that collected information from beneficiary and non-beneficiary families in similar situations in 2005 and 2009. The methodology adopted consists in the association between the methods of Propensity Score Matching (PSM) and Regressions with Fixed Effects, in order to estimate the average treatment effect on the treated (ATT) by difference in differences. The results point to positive effects of the Program on the recently included families, especially regarding the increased children school attendance. Staying in the Program, in turn, favored the increase of school promotion in all income groups and the reduction of repetition for children of families in extreme poverty.